Pengembangan Model Sistem Informasi Aplikasi Helpdesk Online PT. Mustika Memadata - Cadelina Cassandra (Bina Nusantara University, 2015)
The advanced technology and the support of global internet makes it possible to create a system that can support the company or institution effectiveness in providing satisfaction for customers and to fulfill the customer’s needs and requirements. Due to the most important task for the company is to provide a good quality service for the customer, online helpdesk support system also develop quickly nowadays for the reason above. PT. Mustika Memadata is one of the private service company located in Jakarta that has the increase ofcustomer and the limit of human resource. This situation makes the company difficult in monitoring complaints from customer. This paper described the model of proposed helpdesk system to solve the problem. The methodology used in this paper are data collection through study literature review, interview session, directobservation, as well as analysis and design method using OOAD (Object Oriented Analysis and Design) approach using UML diagram such as activity diagram, use case diagram and domain model class diagram. The result is the model design of helpdesk online system that can be used for the company in solving customers’complaint.